Approaching the Concept of Multiliteracies: Multilingual Writing Competence as an Integrated Model - Usanova, Irina; Schnoor, Birger (Canadian Journal of Applied Linguistics, 2022)
In linguistically diverse contexts, language repertoires include various literacy skills in multiple languages across different modes of representation (multiliteracies), where multilingual writing can be conceptualized as a synthesized competence that includes all languages in a person’s repertoire and is continuously evolving. We respond to the call to operationalize existing theory on multilingual writing for empirical testing by conducting first- and second-order confirmatory factor analyses that explore whether and how students’ writing proficiency in different languages can be modelled as an integrated construct, to analyze multilingual writing’s dimensionality. We draw on a corpus of multilingual writing in secondary students (n = 965) in three different languages: the majority language (German), the heritage languages of migrants in Germany (Russian or Turkish), and the first foreign language (English). Based on competence data of a substantial sample of multilingual adolescents, the results provide an empirical approach to modelling multilingual writing competence in complex multilingual repertoires.